2014
DOI: 10.1111/ejss.12216
|View full text |Cite
|
Sign up to set email alerts
|

Soil, food security and human health: a review

Abstract: Direct effects of soil or its constituents on human health are through its ingestion, inhalation or absorption. The soil contains many infectious organisms that may enter the human body through these pathways, but it also provides organisms on which our earliest antibiotics are based. Indirect effects of soil arise from the quantity and quality of food that humans consume. Trace elements can have both beneficial and toxic effects on humans, especially where the range for optimal intake is narrow. We focus on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(135 citation statements)
references
References 149 publications
(179 reference statements)
0
133
1
1
Order By: Relevance
“…However, one commonality with micronutrients in different global agroecosystems is the fact that their deficiency in crops is compounded by a low crop use efficiency (i.e., low crop response per unit of micronutrient, relative to no micronutrient application), typically <10 %, compared to between 20 and 80 % for N, P, and K (Baligar et al 2001). Also, in vast regions of the globe (for instance, in several countries of Africa and Asia), it is reported that majority of the arable land is affected by multiple micronutrient deficiencies (Voortman and Bindraban 2015;Monreal et al 2015;Oliver and Gregory 2015). In these regions, the scenario is further complicated by the inadequate replenishment through fertilization of micronutrients biologically mined from the soil by plant roots, which has had negative agronomic consequences for crop productivity.…”
Section: Micronutrient Deficiencies In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one commonality with micronutrients in different global agroecosystems is the fact that their deficiency in crops is compounded by a low crop use efficiency (i.e., low crop response per unit of micronutrient, relative to no micronutrient application), typically <10 %, compared to between 20 and 80 % for N, P, and K (Baligar et al 2001). Also, in vast regions of the globe (for instance, in several countries of Africa and Asia), it is reported that majority of the arable land is affected by multiple micronutrient deficiencies (Voortman and Bindraban 2015;Monreal et al 2015;Oliver and Gregory 2015). In these regions, the scenario is further complicated by the inadequate replenishment through fertilization of micronutrients biologically mined from the soil by plant roots, which has had negative agronomic consequences for crop productivity.…”
Section: Micronutrient Deficiencies In Soilmentioning
confidence: 99%
“…As such, a micronutrient deficiency in food crops, due to its lack in soil, could translate to micronutrient deficiency in humans (White and Broadley 2009;Martínez-Ballesta et al 2010;Joy et al 2015;Oliver and Gregory 2015). In countries where staple foods consist mainly of cereals and tubers grown in nutrient-poor soils, human micronutrient deficiency, especially of Zn, is widespread, representing a major cause of stunting and child death.…”
Section: Soil Micronutrients In Relation To Human Healthmentioning
confidence: 99%
“…It is necessary for the synthesis of the amino acid selenocysteine, which is involved in the formation of approximately 25-35 proteins (called selenoproteins) that are critical in mammal metabolism (Rayman, 2012;Oliver and Gregory, 2015). Examples of selenoproteins include the glutathione peroxidases (with antioxidant functions), thioredoxin reductases (oxidoreductases that act on disulfide reduction system), iodothyronine deiodinases (responsible for synthesis and metabolic regulation of thyroid hormone) methionine-R-sulfoxide reductase (a zinc-containing selenoprotein), selenophosphate synthetase 2 (synthesis of the active Se donor selenophosphate), 15-kDa selenoprotein (thioredoxin-like fold ER-resident proteins), and selenoproteins H, I, M, T, V, and W (Rayman, 2012;Labunskyy et al, 2014).…”
Section: Importance Of Selenium In Human Healthmentioning
confidence: 99%
“…Such impacts can be direct or indirect. Direct effects are those foremost related to various pathogens contained in the soil (Oliver and Gregory 2015), which children are particularly exposed to (Hawley 1985). Indirect effects are primarily factors such as soil fertility that affect the quantity and quality of food produced (or the kind of food that can be produced).…”
Section: Previous Researchmentioning
confidence: 99%
“…Indirect effects are primarily factors such as soil fertility that affect the quantity and quality of food produced (or the kind of food that can be produced). In addition, trace elements and minerals in the soils are transferred to the food cultivated in it, which in turn affect the health of humans (Abrahams 2002;Oliver and Gregory 2015). For example the availability of elements such as iron, iodine, selenium, and zinc (Oliver and Gregory 2015), which are essential to human health, is highly linked to soil quality.…”
Section: Previous Researchmentioning
confidence: 99%